The Liability of Good Reputation: A Study of Product Recalls in the U.S. Automobile Industry - Rhee, Mooweon; Haunschild, Pamela R. (Organization Science, 2006)
In this paper, we explore opposing theoretical claims about how organizational reputation affects market reactions to product defects. On the one hand, good reputation could be a disadvantage because expectations about product quality are more likely to be violated by defects in highly reputed products. On the other hand, a good reputation could be an advantage because of strong inertial effects on reputation orderings. We empirically test these competing hypotheses using data on product recalls in the U.S. automobile industry from 1975 to 1999. Our results support for the idea that reputation can be an organizational liability in that highly reputed firms suffer more market penalty as a result of their product recalls. We also propose that the reputational effects are moderated by two important factors: substitutability and generalism/specialism. Our results show that having few substitutes with an equivalent level of reputation, or a focused product identity stemming from specialism, buffers the negative market reactions to product recalls. We conclude with a discussion on the implications of these results for institutional, reputation, and status theories.